Optimizations of extraction and separation process of saponins and in vitro antioxidant activity from the female gonad of Apostichopus japonicus - ZHONG Jing-shi; ZHANG Jian; LIU Fang; WANG Gong-ming; WANG Yi-xin (Shipin yu jixie, 2022)
Objective: This study aimed to optimize the ultrasonic-assisted extraction technology and HSCCC separation process of saponins from the female gonad of Apostichopus japonicus and to explore their antioxidant activities. Methods: Extraction time, ethanol concentration, ultrasonic time, and solid-to-solvent ratio as the influencing factors were considered in this study, and the extraction process of saponin was optimized using the response surface methodology. The ratio of solvent systems, the volume flow of mobile phases, and the rotation speeds of HSCCC were optimized. The DPPH radical and ABTS radical scavenging experiments were conducted to evaluate the antioxidant activities of the crude extracts and the separated fractions. Results: The optimal extraction condition of the crude saponin were extraction time of 7 d, ethanol concentration of 83%, ultrasound time of 33 min, and solid-to-solvent ratio of 1∶20 (g/mL). Under these conditions, the extraction rate of saponins was (0.66 ± 0.02)%. Components 1 and 2 were separated from the crude saponin by HSCCC with Vacetate∶Vbutanol∶Vmethanol∶Vwater=2.0∶3.0∶0.2∶4.8, 2 mL/min volume flow, and 800 r/min rotation speed. The DPPH radical scavenging rate of the crude saponin, component 1, and component 2 were (36.23±0.55)%, (35.07±0.20)%, and (38.40±0.14)%, respectively, while the ABTS radical scavenging rate were (17.55±0.42)%, (24.49±0.50)% and (33.65±0.34)%, respectively. Conclusion: A higher yield of crude saponin from the female gonad of Apostichopus japonicus with better separation was obtained after process optimization. Compared with the crude saponin, the antioxidant activity of component 2 was improved after HSCCC separation.